LAMA KEBUNTINGAN MONYET HITAM SULAWESI (Macaca nigra) DI CAGAR ALAM TANGKOKO-BATUANGUS, SULAWESI UTARA - Saroyo Saroyo (The East Java Biological Society, 2009)
A research about gestational length of Sulawesi crested black macaque (Macaca nigra) has conducted to determine the length between conception and birth. Five adult females of Rambo II Group at Tangkoko-Batuangus Nature Reserve, North Sulawesi, were used as samples. Data collection used focal animal sampling to observe the sex swelling cycle and the time when they gave birth. The length of gestation was determined by counting the time duration between middle fully swollen until giving birth. Data was analyzed descriptively to count the mean and standard deviation. Result showed that the gestational length of Sulawesi crested black macaque was 183.6 ± 11.6 days. From this result can be concluded that the gestational length of this species is longer than other Macaca species.